Dysbiosis: A Review Highlighting Obesity and Inflammatory Bowel Disease. (November 2015) - Kim, Adam
Abstract : There are microbes in and on many parts of the human body and all of the microbes that inhabit an ecosystem are the microbiota, which can be commensal, symbiotic, and pathogenic. Alterations in the homeostasis of the microbiota are considered dysbiosis. To determine how changes to the normal flora are associated with disease, we first need to identify normal gut flora. The gold standard for microbiota analysis is currently by 16S rRNA gene amplification techniques. The human diseases, obesity and inflammatory bowel disease, are prime examples of dysbiosis. Both diseases exhibit a decreased diversity of microorganisms and characteristic changes in bacterial phyla as well as evidence of abnormal gut bacterial translocation and inflammation. As standardization of techniques and longitudinal studies come together in multicenter observations of the gut microbiota, a blossoming understanding will inevitably allow us to better diagnose, treat, and possibly even prevent disease.